2019
DOI: 10.1002/ange.201914396
|View full text |Cite
|
Sign up to set email alerts
|

Structure‐Based Design of a Macrocyclic PROTAC

Abstract: Constraining am olecule in its bioactive conformation via macrocyclization represents an attractive strategy to rationally design functional chemical probes.W hile this approach has been applied to enzyme inhibitors or receptor antagonists,t od ate it remains unprecedented for bifunctional molecules that bring proteins together,s uch as PROTAC degraders.H erein, we report the design and synthesis of am acrocyclic PROTACb ya dding ac yclizing linker to the BET degrader MZ1. Aco-crystal structure of macroPROTAC-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 32 publications
(87 reference statements)
0
22
0
Order By: Relevance
“…Structural information on the ternary complexes between target proteins, PROTACs, and E3 ubiquitin ligases is now beginning to allow rational, structure-based design of PROTACs. 4 Design of PROTACs also requires knowledge about how their structures influence their ADME properties, with cell permeability being required for their mode of action. A few recent studies have begun to provide some, albeit sometimes conflicting, insight into how the ADME properties of PROTACs could be optimized.…”
mentioning
confidence: 99%
“…Structural information on the ternary complexes between target proteins, PROTACs, and E3 ubiquitin ligases is now beginning to allow rational, structure-based design of PROTACs. 4 Design of PROTACs also requires knowledge about how their structures influence their ADME properties, with cell permeability being required for their mode of action. A few recent studies have begun to provide some, albeit sometimes conflicting, insight into how the ADME properties of PROTACs could be optimized.…”
mentioning
confidence: 99%
“…We and others have shown that improved PROTAC-induced degradation of BET protein translates to enhanced effect in the viability of BET-dependent cancer cell lines. 38,69 We therefore moved to evaluate the cytotoxicity of our PROTAC series by assessing the viability of BETsensitive lines MV4;11 (acute myeloid leukemia) (Figure 4D) and 22Rv1 (human prostate carcinoma) (Figure 4E). All PROTACs exhibited a marked antiproliferative effect on each cell line, consistent with their activity as degraders.…”
Section: Improving Protac Permeability Increases Protac Bioactivitymentioning
confidence: 99%
“…This allows us to calculate the cooperativity (α) of ternary complex formation (α = Kd binary / Kd ternary , Figure 5C). 34,59,69,[72][73] Figure 5: Fluorescence polarization (FP) of PROTAC binding. Binary and ternary complex formation FP data for amide (A) and ester (B) PROTACs to VHL alone (diamonds and dashed line) or preincubated Brd4 BD2 with PROTAC to VHL (circles and solid line).…”
Section: Improved Potency Is Due To Improved Permeability Rather Than Improvements To Ternary Complex Formationmentioning
confidence: 99%
“…Very recently, a macrocyclic protac has been designed as a conformationally restricted analog of the BET degrader MZ1 [ 168 ]. As it is common in classical drug design, the use of this conformationally restricted analog leads to a more selective degrader with a cellular activity comparable to that of the parent flexible protac.…”
Section: Miscellaneous Protacsmentioning
confidence: 99%